ANALISA CAPAIN PEMBELAJARAN PKL KE-1 JURUSAN TEKNIK RADIODIAGNOSTIK DAN RADIOTERAPI POLTEKKES KEMENKES JAKARTA II: Analysis of Learning Outcomes of the 1st PKL of Radiodiagnostic Engineering and Radiotherapy Department of Poltekkes Kemenkes of Jakarta II - Muhammad Irsal (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2021)
Higher education is responsible for producing graduates who are globally competitive with hard skills and soft skills, one of which is by doing internships, therefore it is necessary to analyze the learning objectives of student internships at the Department of Radiodiagnostic and Radiotherapy, Health Polytechnic of the Ministry of Health Jakarta II to maintain the quality of graduates according to the Indonesian National Qualification Framework. Data collection was carried out on students who were doing their 1st internship in 7 hospitals in the DKI Jakarta area. The data used by giving students pre and post-tests on the understanding of apprenticeship learning, then surveying the number of radiographic examinations that have been carried out by students by the understanding of apprenticeship learning at the hospital. Analysis of decision making based on the understanding of the 1st apprenticeship learning if the pre and post-test percentage value> 50% and analysis of the number of radiographic examinations carried out by students as an indicator for evaluating the understanding of apprenticeship learning. and the post-test percentage value of 70.1% of students can carry out radiographic examinations, with a comparison of the post-test results there is an increase of 12.6% in the learning objectives of the apprenticeship and 31.2% in supporting data information about a clinical experience during the internship, from the pre and post-test> 50%, the understanding of apprenticeship learning has been achieved. Then in analyzing the number of radiographic examinations carried out by students as an indicator of evaluating understanding of apprenticeship learning, it is hoped that the college can evaluate the placement of student hospitals during the internship so that radiographic examinations that have not been fulfilled during the internship can be fulfilled during the following round of internships